Pembelajaran SNBT Pengetahuan Kuantitatif melalui Konten Edukasi YouTube - Syifaul Janan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Many high school students face difficulties in understanding SNBT quantitative knowledge concepts, particularly HOTS questions. This is worsened by limited access to quality learning resources and educational disparities across regions. This community service provides SNBT quantitative knowledge learning through YouTube as an open and accessible medium. Eight instructional videos covering sequences, exponents, numbers, root forms, geometric shapes, statistics, probability, and functions were created using Zoom and published on Faul Mathematics YouTube channel. Results showed 500+ viewers with positive interactions. This demonstrates YouTube-based learning effectively equalizes access to quality mathematics education and supports students' SNBT preparation comprehensively and sustainably.